DECISION SUPPORT SYSTEM OF ACHIEVED STUDENTS USING WEIGHTED PRODUCT METHOD - Dewi Rahayu; Siti Mukodimah (IJISCS (International Journal of Information System and Computer Science), 2019)
Constitution of the Republic of Indonesia No. 12 of 2012 that part of the national education system has a strategic role in educating the life of the nation. Students are people who are trying to develop themselves through the process of education on the path, level and type of education. The Weighted Product method is chosen because the method is solved by using multiplication to connect the value of the attribute, where the value must be raised with the attribute weight value in question. Criteria that have been determined include: average value, discipline, attendance, extracurricular, and Non-Academic. The results of this study there are 6 alternatives, obtained the value of Agus = 0.1618 as the student with the lowest value and the value of Intan = 0.1748 as the best student